Optimizing Learning Strategies For Early Chilhood During The Covid-19 - Mavianti Mavianti; Fildza Hanisa; Suraiya Chapakiya (-, 2023)
This research is motivated by the importance of learning strategies, the learning process cannot work without cooperation between students and teachers. But for now the corona virus has spread in various countries around the world. With the circular issued by the Ministry of Education and Culture no. 4 of 2020 which calls on all educational institutions from the early childhood education level to tertiary institutions not to conduct face-to-face learning in schools and instead study from home through the online system. The process of online and offline learning strategies is expected to be able to make learning interesting, easy to understand and creative. The purpose of this study was to find out the learning strategies used during a pandemic and to find out the supporting and inhibiting factors. This research is a research with a qualitative approach. The results of this study indicate that the learning strategy during the covid-19 pandemic at RA Ummu Zainab used online and offline learning and could collaborate both. The inhibiting factors for offline learning are limited learning time. And the supporting factors for online learning strategies are that they can make better use of technology, parents can be closer to their children, can do it anytime and anywhere according to predetermined hours.